PENGARUH MOTIVASI TERHADAP KUALITAS KARYAWAN DINAS PENDAPATAN DAERAH KOTA SURAKARTA DALAM IMPLEMENTASI STANDAR PELAYANAN : KEPUASAN KERJA DAN TEKANAN KERJA SEBAGAI VARIABEL INTERVENING - Ririk Yunita HKS (MANAJEMEN DAN KEUANGAN, 2007)
The objective of this research is to empirically analyse the impact of motivation, implementation quality of standart service, with job tension and job satisfaction as intervening variable. The result of this research is expected to give contribution in developing the theory, especially concerning teh attitude of public servive staff of Dispenda Kota Surakarta. Path analysis was used to test the hypotheses using SPSS. The result reveals that there is a significant effect between motivation and job satisfaction, between motivation and implementation quality of standart service, and between job satisfaction and implementation quality of standart service. This study also examines two intervening models : (1). Job satisfaction that may intervene the relatonship between motivation and impelementation quality of standart service. (2). Job tension that may intervene the relatonship between motivation and impelementation quality of standart service. The result indicates that job satisfaction intervene the relation between motivation and implementation quality of standart service. Therefore, job tension as intervening variable can be ignored.